2020
DOI: 10.1002/jor.24635
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral symmetry in leg and joint stiffness in children with spastic hemiplegic cerebral palsy during gait

Abstract: Deviations are often identified at individual joints in the gait analysis of patients with cerebral palsy. Previous gait studies on hemiplegic cerebral palsy (HCP) have focused mainly on deviations of the affected side. The current study aimed to quantify and compare the joint and leg stiffness, the contributions of skeletal and muscular components, and the associated joint angles and moments of the affected and nonaffected lower limbs during level walking in children with spastic HCP. A total of 12 children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Fe(t) is effective GRF, Le (t) is effective leg length and φ(t) is the angle between the longitudinal axis of the shank and the line joining the COP to the center of the hip joint. KT is defined as the sum of KL of the left leg (KLL) and KL of the right leg (KRL) (Adapted from [14]). The proportional share, KS(t), was then time-averaged over the double-limb support phases of gait (i.e., LR and PS).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Fe(t) is effective GRF, Le (t) is effective leg length and φ(t) is the angle between the longitudinal axis of the shank and the line joining the COP to the center of the hip joint. KT is defined as the sum of KL of the left leg (KLL) and KL of the right leg (KRL) (Adapted from [14]). The proportional share, KS(t), was then time-averaged over the double-limb support phases of gait (i.e., LR and PS).…”
Section: Figurementioning
confidence: 99%
“…Thus, very few studies have examined how the lower limbs coordinate with each other for the observed gait patterns, especially during weight transfer between limbs in DLS. Previous studies have shown that leg stiffness, incorporating information of both the kinematics and kinetics of the lower limb joints, is a useful measure and should be included in future clinical gait analysis for a more complete assessment of gait in children with CP [13][14][15]. For assessing the effects of pathology and the efficacy of TRS on the inter-limb coordination and bilateral symmetry in body-weight transfer and balance control during CP gait, quantitative analysis of leg stiffness during the phases of gait for both limbs can be a useful approach.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the extent of the secondary movement disorder (secondary deviation of the involved limb) is dependent on the primary brain lesion [1,[4][5][6]. The secondary deviation itself causes adaption/compensatory movement patterns (tertiary deviation) of the uninvolved limb [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in unilateral CP, the naturally given asymmetry and consecutive highly complex movement patterns of the disorder on the one hand, and the ability of the sound limb concerning functional strategies to compensate on the other hand, affect the overall functional impairment, which is commonly classified using the Gross Motor Function Classification System (GMFCS) [8,9,17]. The functional capabilities of the sound limb are highly relevant for the overall propulsion and stability of walking [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation